Pengaruh Model Pembelajaran Kooperatif Tipe NHT Terhadap Hasil Belajar Budaya Hidup Sehat Ditinjau Dari Motivasi Belajar Pada Masa Pandemi Covid-19 - Ni Luh Putu Lindiana Oktaviyanti Utami; I Gusti Lanang Agung Parwata; Suratmin Suratmin (Journal on Education, 2023)
The purpose of this study was to determine the effect of the NHT learning model on the learning outcomes of a healthy lifestyle in terms of students' learning motivation. The type of research used is a quasi-experimental design with Treatment by Level with two categories of 2 x 2. The research subjects were 40 students who were divided into 2 groups of learning models. Data were analyzed using descriptive analysis and analysis of covariance (two-way ANOVA) with 95% confidence level (α = 0.05). The findings of this study are differences in learning outcomes between students using the NHT method and conventional learning. There is an interaction between students who use the NHT learning model and the conventional learning model. There is a difference between students with high learning motivation and low learning motivation in the NHT learning model. There are differences in learning outcomes between students with high motivation and low motivation in conventional learning models. The NHT learning model is a learning strategy that can improve student learning outcomes in learning healthy lifestyle materials during the COVID-19 pandemic. By applying this learning model in PJOK learning, it is expected that students can improve learning outcomes and learning motivation which plays an important role in improving learning achievement. The purpose of this study was to determine the effect of the NHT learning model on the learning outcomes of a healthy lifestyle in terms of students' learning motivation. The type of research used is a quasi-experimental design with Treatment by Level with two categories of 2 x 2. The research subjects were 40 students who were divided into 2 groups of learning models. Data were analyzed using descriptive analysis and analysis of covariance (two-way ANOVA) with 95% confidence level (α = 0.05). The findings of this study are differences in learning outcomes between students using the NHT method and conventional learning. There is an interaction between students who use the NHT learning model and the conventional learning model. There is a difference between students with high learning motivation and low learning motivation in the NHT learning model. There are differences in learning outcomes between students with high motivation and low motivation in conventional learning models. The NHT learning model is a learning strategy that can improve student learning outcomes in learning healthy lifestyle materials during the COVID-19 pandemic. By applying this learning model in PJOK learning, it is expected that students can improve learning outcomes and learning motivation which plays an important role in improving learning achievement.